Experiment Study on Improving Water-Cooled Air Conditioner Performance with High Efficiency Condenser - 黄德斌; 欧阳惕; 潘永昌; 张建学; 朱冬生 (Zhileng xuebao)
A rod-baffle condenser with spirally corrugated and sawtooth-shaped finned tube was used in a water-cooled air conditioner system. The testing result shows that this air conditioner has higher performance. Compared with air conditioners using normal finned tube( lower fin) condenser,the refrigerating capacity of this air conditioner increases by 3.7% and energy efficiency ratio increases by 8.5% while heat transfer area of the condenser decreases by 37.5% under the rated working conditions and using R22 as refrigerant.